Indonesia matters : Asia's emerging democratic power - Acharya, Amitav, (World Scientific, 2014)
"[This book] analyses Indonesia's foreign policy and international role under the democratic regime, with particular focus on its role as a leader of ASEAN, its relationship with the major powers of the Asia Pacific, and its place in global order of the 21st century"--